1990
DOI: 10.1073/pnas.87.8.2892
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of potassium currents in single myometrial cells.

Abstract: Three potassium currents (IK) were recorded from myometrial cells isolated from the uterus of rats at estrus and diestrus and kept in culture for 1-6 days. IK were differentiated by their modulation with norepinephrine and/or by their onset kinetics. At +50 mV the activation time constants were about 0.7 ms, 6 ms, and 15 ms for the fast, the intermediate, and the slow 'K, respectively. Norepinephrine (1 ,IM) potentiated the fast IK and reduced the intermediate IK. In addition, differences were found with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…The rapidly inactivating 4-AP-sensitive K ϩ current is prominent in myometrial cells (11,19,22,25,30,31) and plays an important role in controlling membrane potential during gestation (19,25). The kinetics and pharmacological properties of this current resemble those produced by channel subunits in the Kv4 family.…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly inactivating 4-AP-sensitive K ϩ current is prominent in myometrial cells (11,19,22,25,30,31) and plays an important role in controlling membrane potential during gestation (19,25). The kinetics and pharmacological properties of this current resemble those produced by channel subunits in the Kv4 family.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of glibenclamide on 86Rb efflux and contractions in cyanide A variety of K+ channels have been described in the uterus (Toro, Stefani & Erulkar 1990) (Standen, Quayle, Davies, Brayden, Huang & Nelson, 1989;Piper, Minshall, Downing, Hollingsworth & Sadraei, 1990). The effects of glibenclamide (20 #M) on the rate constant of 86Rb efflux in cyanide were therefore examined.…”
Section: Resultsmentioning
confidence: 99%
“…Thus although gestational conditions may alter K+ channel conductances in the uterus (Toro et al 1990), such changes were not influencing the response to cyanide. The greater depression of contraction by cyanide in nonpregnant compared to pregnant uteri must reside in some other effect of cyanide; for example, the greater fall in [ATP] and [PCr] (Wray, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…While the physiological role of minK channels in heart and epithelial cells becomes apparent (Busch et al 1994;Wangemann et al 1995;Suessbrich et al 1996), their role in the uterus remains unclear. The excitability of uterus during pregnancy is controlled by the estrogen blood concentration which influences the expression of a number of distinct ion channels (for review see Parkington and Coleman 1988;Toro et al 1990). For rat uterus it was shown that minK RNA is dramatically increased at high estrogen blood concentrations (Folander et al 1990), and a role for minK in labour induction has been proposed (Boyle et al 1987).…”
Section: Introductionmentioning
confidence: 99%